Redox properties of polyelectrolyte multilayer modified electrodes: a significant effect of the interactions between the polyelectrolyte layers in the films. (1st February 2017) - Strawski, Marcin; Granicka, Ludomira H.; Szklarczyk, Marek
Abstract: The layer-by-layer (LbL) sequential adsorption of oppositely charged polyelectrolytes leads to the formation of multilayered films (Polyelectrolyte Multilayer, PEM). Such systems may find application as ultrathin membranes with controlled properties. In this paper we examine different polyelectrolyte multilayers formed from poly-L-lysine (PLL), polyethyleneimine (PEI), poly(sodium 4-styrenesulfonate) (PSS) and alginate (ALG) polyelectrolytes. Film thicknesses for the PLL/PSS, PLL/ALG and PEI/PSS combinations showed similar values of up to 14 nm on mica and ca. 22 nm on platinum surfaces. The PEI/ALG combination formed thicker films with thicknesses of up to 90 nm on mica and ca. 140 nm on platinum surfaces. For the prepared films, the electroactive behavior towards [Fe(CN)6 ] 3−/4− and [Ru(NH3 )6 ] 3+/2 ions was monitored. We found that the oxidation/reduction current of [Fe(CN)6 ] 3−/4− ions showed three different modes of behavior which can be described as non-permeability, permeability and accumulation of ions. For [Ru(NH3 )6 ] 3+/2+ such a relation was not observed and all of the films remained permeable. The permeability of the thin PEMs seems to depend more strongly on the film composition than the film thickness. The best candidate for encapsulation purposes is proposed.